USP-IRETA / CTA Regional Workshop on Food Processing and Value Adding in the Pacific - Umar, Mohammed; Tulua, Joycemaurie; Prasad, Ritesh Rohit (IRETA, 2006)
The objective of this workshop was to promote additional appropriate technologies to encourage promotion of the processing sector at both the commercial and village level.